(untitled) (Research, Society and Development, 2022)
The purpose of this study is to discuss the Distance Education teaching modality as a tool for the democratization and access to continuing education courses on the environmental aspect aimed at professionals in the Education area of the Municipal Department of Education of Moju-Pará. The methodology used in the research was in the form of a field study, through the quantitative-qualitative approach based on interdisciplinarity and the definition of a single municipality for analysis that consolidates the case study method. As the main instrument for the constitution of the data, a semi-structured interview was used with the course participants who had graduated from the Improvement Course in Environmental Education, as well as simple observation and document analysis as accessory procedures. The results of the discussion and the analysis of the data showed that this training process, carried out in the Distance Education teaching modality, met the needs and expectations of the course participants since the majority indicated this teaching modality as the only possibility for carrying out processes of continuing education. Furthermore, the research subjects highlighted the autonomy and flexibility of schedules as the main advantages for courses carried out in this teaching format, even though they have also signaled obstacles such as poor internet quality and the need for greater interaction with teachers and classmates.